2015
DOI: 10.1517/13543776.2015.1012155
|View full text |Cite
|
Sign up to set email alerts
|

Bcr-Abl tyrosine kinase inhibitors: a patent review

Abstract: The search for Bcr-Abl inhibitors is very active. We believe that a number of patented compounds could enter clinical trials and some could be approved for CML therapy in the next few years. Overall, Bcr-Abl inhibitors constitute a very appealing research field that can be expected to expand further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…ABL1 (Abelson tyrosin protein kinase 1), located on 9q34, is a proto‐oncogene with cell cycle function involved in a variety of cellular processes, including cell division, adhesion and differentiation. It is known to be involved in myeloid and lymphoblastic leukemias as part of the Philadelphia chromosome …”
Section: Discussionmentioning
confidence: 99%
“…ABL1 (Abelson tyrosin protein kinase 1), located on 9q34, is a proto‐oncogene with cell cycle function involved in a variety of cellular processes, including cell division, adhesion and differentiation. It is known to be involved in myeloid and lymphoblastic leukemias as part of the Philadelphia chromosome …”
Section: Discussionmentioning
confidence: 99%
“…Type I, II and IV TKIs, including imatinib, nilotinib, dasatinib, bosutinib and ponatinib, have shown activity against Bcr-Abl and have been approved by the FDA (Figure 2), and about 36 compounds have been patented during the last 8 years [9]. Nevertheless, imatinib has been shown to lose its effectiveness against CML in up to 30% of patients during their first five years on therapy [10].…”
Section: Figure 1 Schematic Representation Of the Moieties In Imatinmentioning
confidence: 99%
“…Because this mutation occurs at the gatekeeper site and may cause steric hindrance precluding the access of the inhibitors to ATP-binding pocket [4], the discovery of potent Bcr-Abl inhibitors targeting T315I mutation would have important implications to treat the most clinically promising Abl T315I mutant therapies. Several new compounds, such as ponatinib [5] and rebastinib [6], have been studied clinically for CML patients harboring the Bcr-Abl T315I mutation, and it has shown that the Bcr-Abl inhibitors targeting the T315I mutant can inhibit the full range of Bcr-Abl kinase domain mutations as well as the wild-type kinase [7].…”
Section: Introductionmentioning
confidence: 99%